Preparation method and application of aluminum-doped noble metal nano-catalyst
By preparing aluminum-doped precious metal nanocatalysts, the problem that existing catalysts are prone to poisoning in the presence of carbon monoxide is solved, the catalytic performance and anti-toxicity of fuel cells are improved, and the production cost is reduced.
Patent Information
- Application Number
- CN202411615652.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
Existing proton exchange membrane fuel cell catalysts are easily poisoned in the presence of carbon monoxide, resulting in catalyst structure damage and battery performance degradation, limiting the application scenarios of batteries.
The preparation method of aluminum-doped precious metal nanocatalyst is adopted. By mixing carbon source, aluminum salt and 2-methylimidazole with noble metal solution, pyrolytic treatment is carried out at high temperature to form an aluminum-doped precious metal carbon composite material, and the catalyst resistance is improved. Carbon monoxide toxicity.
It enhances the catalyst's anti-carbon monoxide poisoning ability, improves the catalytic performance of fuel cells, extends the service life of the catalyst, reduces the use of precious metals, and reduces production costs.
Smart Images

Figure CN119481111A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of noble metal catalysts, and in particular relates to a preparation method and application of an aluminum-doped noble metal nanocatalyst. Background Art
[0002] Proton exchange membrane fuel cells have been widely used due to their low pollution and high energy characteristics. How to improve their performance has also become a research hotspot. Therefore, people have begun to turn their attention to the modification of catalysts. In proton exchange membrane fuel cells, catalysts, as the core part, participate in the entire reaction process. They can accelerate the conversion of oxygen and hydrogen into ions, improve their conversion rate, and enhance the performance of the battery. However, industrial hydrogen production is inevitably accompanied by the mixing of carbon monoxide, and even at extremely low concentrations, carbon monoxide will react with the catalyst, destroying the catalyst structure, causing it to lose its catalytic performance, resulting in a decrease in battery performance and loss of use value. These factors greatly limit the application scenarios of batteries. Therefore, there is an urgent need to develop catalysts that can resist carbon monoxide poisoning.
[0003] At present, the catalyst used in hydrogen oxidation is mainly a platinum-carbon system, which fixes the platinum sites by loading platinum on a carbon skeleton, and enhances the battery performance by platinum catalysis of gas. In terms of resisting carbon monoxide poisoning, platinum-ruthenium alloy has been proven to be a good alloy system with good anti-poisoning effect, but platinum-ruthenium, as a precious metal, is very expensive and difficult to industrialize. Therefore, people have gradually turned their attention to non-precious metal catalysts, improving their resistance to carbon monoxide through the interaction between non-precious metal elements and platinum, enhancing the dispersibility of platinum particles, and improving the utilization rate of platinum. Summary of the invention
[0004] In view of these problems, the present invention adds a carbon source, an aluminum salt and 2-methylimidazole into dimethyl sulfoxide respectively and mixes them evenly to obtain a precursor, and then mixes the precursor with a noble metal solution, and pyrolyzes it in a reducing atmosphere at high temperature to obtain a catalyst, thereby enhancing the ability to resist carbon monoxide toxicity and accelerating the generation of H ions in the battery, thereby effectively improving the catalytic performance of the fuel cell.
[0005] In order to achieve the above object, on the one hand, the present invention provides a method for preparing aluminum-doped noble metal nanocatalyst, comprising the following steps: (1) adding a carbon source, 2-methylimidazole and an aluminum salt into an organic solvent, respectively, and performing ultrasonic dispersion, and then stirring to obtain a prepolymer mixed solution; (2) centrifuging the prepolymer mixture of step (1), washing and drying the centrifuged product to obtain a prepolymer material; (3) After dispersing the precursor material in step (2) with a solvent, a certain amount of precious metal aqueous solution is added in batches and fully mixed, followed by centrifugation, washing, and drying. The dried solid product is heat-treated under a reducing gas to obtain a catalyst. Furthermore, the noble metal element is one or more of platinum, palladium, gold, and iridium, preferably platinum.
[0006] Furthermore, the aluminum salt is one or a combination of aluminum acetylacetonate, aluminum chloride, aluminum nitrate, and aluminum acetate; preferably aluminum acetylacetonate.
[0007] Furthermore, in step 1), the organic solvent is one or a combination of methanol, ethanol, dimethyl sulfoxide and water, preferably dimethyl sulfoxide; the carbon source is one or a combination of Ketjen black, graphene, carbon nanotubes, and BP-2000.
[0008] Furthermore, the solvent used for washing in step 2) is one or a combination of methanol, ethanol and acetone.
[0009] Furthermore, the noble metal source in the noble metal solution in step 3) is one or a combination of acetylacetonate, iodide, chloride of the noble metal, and the solvent for dispersing the precursor is one or a mixture of water, acetone, ethanol.
[0010] Furthermore, the mass ratio of the precious metal to aluminum in step (3) is 1: 2.25-36; preferably 1: 4.5-18.
[0011] Furthermore, in step (1), the molar ratio of the aluminum salt to 2-methylimidazole is 1:0.5-8; preferably, the molar ratio of the aluminum salt to 2-methylimidazole is 1:1-4.
[0012] Furthermore, in step (3), the concentration of the noble metal aqueous solution is 10-60 g / L, preferably 15-25 g / L; the reducing gas is a mixture of hydrogen and argon, wherein hydrogen accounts for 5 to 10 vol%, a mixture of ammonia and argon, wherein ammonia accounts for 5 to 10 vol%, a mixture of carbon monoxide and argon, wherein carbon monoxide accounts for 5 to 10 vol%, or a mixture of the above; the heat treatment temperature is 600 to 1000 ° C, the time is 1 to 3 hours, and the heating rate is 1-10 ° C min -1 .
[0013] Furthermore, in step (1), the ultrasonic stirring time is 20-40 min, and in step 2), the stirring time is 8-20 h, preferably 12 h; in step 1), the stirring time is 8-20 h, preferably 12 h; and the stirring speed is 3000 ~ 5000 rpm.
[0014] On the other hand, the present application also provides an application of the catalyst prepared by the above preparation method in a fuel cell.
[0015] The beneficial effects of the present invention are as follows: (1) Organic solvents and organic matter are used to introduce doping atoms, sulfur and nitrogen are doped on carbon, and the precious metal ions are fixed on the polymer skeleton formed by organic matter. After high-temperature pyrolysis, aluminum-doped precious metal carbon composites are prepared. The precious metal atoms and aluminum atoms are aggregated into nanoclusters and can be evenly distributed on the sulfur- and nitrogen-doped carbon carrier to maximize the active sites.
[0016] (2) Aluminum doping affects the d-band electronic structure of precious metal nanoclusters and improves their catalytic activity. The carbon structure doped with sulfur and nitrogen can reduce the absorption of carbon monoxide by adjusting the number of electrons on the carbon surface and reducing the closeness of the connection with the oxygen group, thereby enhancing the ability to resist carbon monoxide toxicity and accelerating the generation of H ions in the battery, effectively improving the catalytic performance of the fuel cell.
[0017] (3) By continuously optimizing the raw material ratio in the preparation process, the utilization rate of precious metal sites is improved, thereby reducing the amount of precious metals used, thereby achieving strong catalytic performance even with a low precious metal content. At the same time, the doped aluminum element is affordable, which can reduce industrial costs in actual production and promote the expansion of industrial scale. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is the XRD pattern of the sulfur-nitrogen-doped carbon-supported platinum-aluminum nanoparticle material prepared in Example 1 of the present invention; Figure 2 This is a SEM image of the sulfur-nitrogen doped carbon-supported platinum-aluminum nanoparticle material prepared in Example 1; Figure 3 This is a diagram showing the catalytic performance of the sulfur-nitrogen-doped carbon-supported platinum-aluminum nanoparticle material prepared in Example 1 under hydrogen and nitrogen; Figure 4 A comparison chart of power density and current density of the sulfur-nitrogen-doped carbon-supported platinum-aluminum nanoparticle material prepared in Example 1 and the catalyst in Comparative Example 1 at different carbon monoxide concentrations; Figure 5 These are some implementation cases, comparative case 1, and comparative case 2, and the electrochemical performance test results at a current of 10A. Specific embodiment: To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0020] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0021] Example 1 A sulfur-nitrogen doped carbon-supported platinum-aluminum nanoparticle material, the preparation method of which comprises the following steps: 1) Add 0.648 g of aluminum acetylacetonate (Ron, AR grade) to 30 ml of dimethyl sulfoxide and perform ultrasonic stirring to obtain an aluminum acetylacetonate mixed solution. Add 0.1 g of Ketjen black and 0.336 g of 2-methylimidazole (Aladdin, >98%) to 30 ml of dimethyl sulfoxide, stir thoroughly with a glass rod, then slowly add the mixture to the aluminum acetylacetonate mixed solution and perform ultrasonic stirring for 30 min to obtain a precursor solution. 2) The precursor solution obtained in step 2) was subjected to magnetic stirring for 12 h, the product was collected by centrifugation, washed with anhydrous ethanol, and finally dried to obtain Al@NSC material; 3) After the Al@NSC material obtained in step 2) was redispersed with anhydrous ethanol, 240 μL of platinum chloride aqueous solution (25 g / L) was added in batches, and magnetic stirring was performed for 3 h. After the precipitate was collected by centrifugation, it was washed with anhydrous ethanol and dried to obtain the Pt-Al@NSC precursor material; 4) The precursor material obtained in step 3) was heated to 400°C under argon, kept at this temperature for 1 h, then heated to 800°C, kept at this temperature for 2 h, and cooled naturally to obtain the Pt-Al@NSC material.
[0022] Example 2 Compared with Implementation Example 1, the mass of aluminum acetylacetonate was changed to 1.296 g, and other conditions remained unchanged.
[0023] Example 3 Compared with Implementation Case 1, the mass of aluminum acetylacetonate was changed to 0.324 g, and other conditions remained unchanged.
[0024] Example 4 Compared with Implementation Case 1, the mass of aluminum acetylacetonate was changed to 2.592 g, and other conditions remained unchanged.
[0025] Example 5 Compared with Implementation Example 1, the mass of aluminum acetylacetonate was changed to 0.162 g, and other conditions remained unchanged.
[0026] Example 6 Compared with Implementation Case 1, the mass of 2-methylimidazole was changed to 0.672 g, and other conditions remained unchanged.
[0027] Example 7 Compared with Implementation Case 1, the mass of 2-methylimidazole was changed to 0.168 g, and other conditions remained unchanged.
[0028] Example 8 Compared with implementation case 1, the stirring time of step 2) was changed to 8 h, and other conditions remained unchanged.
[0029] Example 9 Compared with Example 1, the volume of the added platinum chloride solution was changed to 300 μl, and other conditions remained unchanged.
[0030] Example 10 Compared with Example 1, the volume of the added platinum chloride solution was changed to 60 μl, and other conditions remained unchanged.
[0031] Embodiment 11 Compared with Implementation Case 1, the proportion of platinum chloride in the solution was changed to 50 g / L, and other conditions remained unchanged.
[0032] Example 12 Compared with Implementation Case 1, the proportion of platinum chloride in the solution was changed to 12.5 g / L, and other conditions remained unchanged.
[0033] Embodiment 13 Compared with implementation case 1, the stirring time of step 2) was changed to 20 h, and other conditions remained unchanged.
[0034] Comparative Example 1 Compared with Implementation Case 1, in the electrochemical test, a commercial platinum-carbon catalyst (Hesen, 20%wt) was used for the test, and other conditions remained unchanged.
[0035] Comparative Example 2 Compared with Implementation Example 1, the aluminum salt is replaced with an equimolar amount of aluminum chloride, and other conditions remain unchanged.
[0036] The SEM image of Example 1 of the present invention is as follows: Figure 2 As shown, the material forms a dispersed ZIF structure, and the particles interact with each other, which makes it have good dispersion and improves the utilization of Pt.
[0037] The catalyst obtained in Example 1 was subjected to conventional three-electrode testing using hydrogen and nitrogen respectively. The results are as follows: Figure 3 As shown, the catalyst obtained in Example 1 has high catalytic ability.
[0038] The catalysts obtained in Example 1 and Comparative Example 1 were subjected to membrane electrode tests. The anode gas was pure H2, 1000ppm CO / H2, 2000ppm CO / H2, 5000ppm CO / H2 and 10000ppm CO / H2, respectively, and the cathode gas was air. The results are as follows: Figure 4 The catalytic performance of the catalyst obtained in Example 1 in the presence of carbon monoxide is higher than that of ordinary commercial catalysts.
[0039] The catalysts obtained in Examples 1 to 2 of Implementation Cases 1, 6, 8, 9 and 11 were subjected to membrane electrode tests. When the anode gas was a mixture of hydrogen and a certain concentration of carbon monoxide and the cathode gas was air, the results were as follows: Figure 5 As shown, by comparison, the catalytic performance of implementation case 1 is higher than that of other cases. The doping of N and S elements with carbon forms a composite carrier, which has a synergistic effect with the PtAl alloy, can reduce the adsorption of carbon monoxide and improve the catalyst's resistance to carbon monoxide poisoning. When the same molar amount of aluminum is added, the aluminum salt formed by the reduction of aluminum acetylacetonate has a stronger adhesion ability, which can ensure the single atomic structure of the catalyst and avoid the appearance of clusters, better play the role of aluminum salt in dispersion, ensure the contact area between platinum and gas, and improve the catalytic performance.
[0040] Table 1 shows the half-wave unit performance of the catalysts prepared in Examples 1-13. By comparing the electrochemical performance of the catalysts in Examples 1-5, it can be seen that when the mass ratio of aluminum to platinum metal is 4.5-18:1, the catalyst has a higher half-wave potential and exhibits better catalytic performance. Aluminum and platinum in this range are more conducive to the formation of aluminum-platinum nanoclusters and more conducive to the single-atom dispersion of platinum and aluminum. At the same time, through Examples 1-7, it is found that the change in the addition amount of aluminum acetylacetonate and 2-methylimidazole will also affect the formation of nanoclusters and the single atoms of platinum and aluminum in the clusters. The formation of , finally brought about a change in the performance of the catalyst. When the molar ratio of aluminum acetylacetonate and 2-methylimidazole was 1:1-4, the performance of the catalyst had a higher half-wave potential. It was also found that the stirring time of aluminum atoms also directly affected the formation of platinum and aluminum single atoms in the nanoclusters. It can be seen from Examples 8 and 13 that compared with Example 1, too long or too short stirring time also caused a decrease in catalyst performance. It can be seen that the implementation conditions of Implementation Case 1 are the best conditions, and its half-wave potential reaches 8.83V, which is much higher than other embodiments. The catalyst in Example 1 not only has a better addition ratio, but also has excellent hydrogen oxidation catalytic performance and anti-carbon monoxide poisoning performance, and has better commercial value.
[0041] Table 1
[0042] Compared with commercial Pt / C catalysts, the Pt-Al@NSC composite catalyst prepared by the present invention separates platinum atoms from each other through the doping of aluminum salts, forms nanoclusters with aluminum atoms, and further disperses on the sulfur-nitrogen doped carbon carrier, increases the contact between platinum and gas, and maximizes the catalytic effect of platinum in the reaction, improves the utilization rate of platinum, reduces the input of platinum metal, and reduces costs. In addition, due to the special structure formed by aluminum salts and nitrogen and sulfur, the catalyst can still maintain good performance when the anode gas contains a certain amount of carbon monoxide, and the anti-carbon monoxide performance is greatly improved compared with commercial catalysts. In practical applications, it can adapt well to relatively harsh environments and has certain practical significance in the application field of proton exchange membrane fuel cells.
[0043] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A method for preparing aluminum-doped noble metal nanocatalyst, characterized in that: The steps include: (1) adding a carbon source, 2-methylimidazole and an aluminum salt into an organic solvent, respectively, and performing ultrasonic dispersion, and then stirring to obtain a prepolymer mixed solution; (2) centrifuging the prepolymer mixture of step (1), washing and drying the centrifuged product to obtain a prepolymer material; (3) After dispersing the precursor material in step (2) with a solvent, a certain amount of precious metal aqueous solution is added in batches and fully mixed, followed by centrifugation, washing, and drying. The dried solid product is heat-treated under a reducing gas to obtain a catalyst.
2. The preparation method according to claim 1, characterized in that: The noble metal element is one or more of platinum, palladium, gold and iridium, preferably platinum.
3. The preparation method according to claim 1, characterized in that: The aluminum salt is aluminum acetylacetonate, aluminum chloride, aluminum nitrate, aluminum acetate, or a combination thereof; preferably aluminum acetylacetonate.
4. The preparation method according to claim 1, characterized in that: In step 1), the organic solvent is one or a combination of methanol, ethanol, dimethyl sulfoxide and water, preferably dimethyl sulfoxide; the carbon source is one or a combination of Ketjen black, graphene, carbon nanotubes and BP-2000.
5. The preparation method according to claim 1, characterized in that: The noble metal source in the noble metal solution in step 3) is one or a combination of acetylacetone compounds, iodides, and chlorides of noble metals, and the solvent for dispersing the precursor is one or a mixture of water, acetone, and ethanol.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the noble metal element to the aluminum element in step (3) is 1: 2.25-36; preferably 1: 4.5-18.
7. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of the aluminum salt to 2-methylimidazole is 1:0.5-8, and preferably the molar ratio of the aluminum salt to 2-methylimidazole is 1:1-4.
8. The preparation method according to claim 1, characterized in that: In step (3), the concentration of the noble metal aqueous solution is 10-60 g / L, preferably 15-25 g / L; the reducing gas is a mixture of hydrogen and argon, a mixture of ammonia and argon, a mixture of carbon monoxide and argon, or a mixture of several thereof; the heat treatment temperature is 600-1000 °C, the time is 1-3 h, and the heating rate is 1-10 °C·min -1 .
9. The preparation method according to claim 1, characterized in that: In step (1), the ultrasonic stirring time is 20-40 min; the stirring time in step 1) is 8-20 h, preferably 12 h; the stirring speed is 3000 ~ 5000 rpm.
10. Use of the catalyst prepared by the preparation method according to any one of claims 1 to 10 in a fuel cell.
Citation Information
Patent Citations
Metal monatomic site catalyst and preparation method and application thereof
CN111359629A
Preparation method of cobalt and nitrogen doped carbon-based catalyst and application of cobalt and nitrogen doped carbon-based catalyst in electrochemical catalytic synthesis of hydrogen peroxide
CN113789544A
High-load and high-dispersion Cu-based catalyst as well as synthesis method and application thereof
CN117138784A
Metal-doped organometallic-carbon composite and manufacturing method the same
KR101881949B1